Circulating tumor DNA strongly predicts efficacy of chemotherapy plus immune checkpoint inhibitors in patients with advanced gastro-esophageal adenocarcinoma - David Tougeron; Christophe Louvet; Jérôme Desramé; Ludovic Evesque; Antoine Angelergues; Aurélien Carnot; Gilles Breysacher; Aziz Zaanan; Nicolas Etchepare; May Mabro; Laure Kaluzinski; Caroline Petorin; et al. (Communications Medicine)
Abstract Background Efficacy of 2nd line treatment in advanced gastric or gastro-esophageal junction (GEJ) adenocarcinoma remains limited with no identified strong predictor of treatment efficacy. We evaluated the prognostic value of circulating tumor DNA (ctDNA) in predicting the efficacy of immune checkpoint inhibitors (ICI) plus chemotherapy in the randomized PRODIGE 59-FFCD 1707-DURIGAST trial. Methods ctDNA was evaluated before treatment (baseline) and at 4 weeks (before the third cycle of treatment, C3) using droplet-digital PCR assays based on the detection of CpG methylation. Results Progression-free survival (PFS) and overall survival (OS) were shorter in patients with a high (>1.1 ng/mL) versus low (<1.1 ng/mL) ctDNA concentration at baseline (2.3 vs. 5.8 months; HR = 2.19; 95% CI, 1.09–4.41; p = 0.03 and 4.5 vs. 12.9 months; HR = 2.73; 95% CI, 1.29–5.75; p < 0.01), respectively, after adjustment for identified prognostic variables. Patients with a ctDNA decrease ≤75% between baseline and C3 versus a ctDNA decrease >75% had a worse objective response rate (p = 0.007), shorter PFS (2.2 vs. 7.4 months, HR = 1.90; 95% CI, 1.03–3.51; p = 0.04) and OS (6.6 vs 16.0 months; HR = 2.18; 95% CI, 1.09–4.37; p = 0.03). Conclusions An early decrease in ctDNA concentration is a strong predictor of the therapeutic efficacy of ICI plus chemotherapy in advanced gastric/GEJ adenocarcinoma. Clinical Trial Information NCT03959293 (DURIGAST).